Pemilihan bank dari sudut kualiti perkhidmatan menggunakan proses hierarki analisis - Aida Othman,; Wan Rosmanira Ismail , (Penerbit ukm, 2008)

(untitled)
The purpose of this research is to identify the priority of the dimensions considered by bank users in terms of the service quality framework known as SERVQUAL. Three bank branches; Bank Islam, Maybank and BCB are used as alternatives and the importance of dimension and atributs of service quality are then obtained from these three banks. The Analytical Hierarchy Process method is used to obtain the weights of each dimension and atributs of SERVQUAL. The results obtained showed that banks' users' priority is assurance and this result is different from those obtained in the previous studies. It may be due to the fact that the criteria used in the previous researches are more general and not focused on service quality. According to the atributes, the customers prefer knowledgable staffs who can help them in speeding up their business in the bank. The study showed that Maybank is rated first, followed by BCB and Bank Islam based on the weights obtained in service quality